Time Scales of Benthic Macrofaunal Response to Pelagic Production Differ Between Major Feeding Groups - Lessin, Gennadi; Bruggeman, Jorn; McNeill, Caroline Louise; Widdicombe, Stephen (Frontiers in Marine Science, 2019)
Benthic macrofauna, as an element of rich and diverse benthic communities of the shelf seas, play a key role in marine biogeochemical cycles and support a wide range of ecosystem services. To better understand how macrofauna affects mass and energy fluxes within the seabed and between the bed and the pelagic, it is fundamental to characterise their structural and dynamic response to the quantity, quality and timing of food supply. To do so, we have combined long-term time-series of pelagic productivity and macrofaunal abundance with a model of benthic food web to: (1) estimate the characteristic response time scales of major groups of benthic macrofauna to food availability, (2) relate these to carbon fluxes within sediments and across the benthic–pelagic boundary, and (3) explore the mechanisms responsible. The model was designed as a canonical representation of the benthic system, retaining the key pathways that connect benthic macrofauna to pelagic environment, but aggregating variables and groups that were not explicitly observed. Both observations and model simulations revealed pronounced differences between deposit and suspension feeders in their rate of response to phytoplankton blooms: deposit feeders showed a dampened response lagging 26–125 days behind the peak in pelagic production, while suspension feeders responded rapidly, within only 5–7 days. The model parametrisation obtained during calibration relates this to differences in feeding modes, in (trophic) proximity to primary production and in rates of ingestion and losses. Specifically, suspension feeders are predicted to act as a gateway to pelagic productivity, controlling the quantity of organic carbon reaching sediment-dwelling fauna.